PATHOMORPHOLOGICAL CHANGES IN LIVER OF WHITE MICE AT EXPERIMENTAL PLAGUE INFECTION CAUSED BY YERSINIA PESTIS OF DIFFERENT PLASMID COMPOSITION - V. I. Dubrovina; T. P. Starovoytova; S. A. Vityazeva; G. B. Mukhturgin; M. Y. Kotlov; S. V. Balakhonov (Acta Biomedica Scientifica, 2017)
Data of histological study of pathomorphological changes in liver of white mice with experimental plague are represented in the article. An important element in evaluation and prediction of the pathological process in the liver is the analysis of hepatocyte karyokinesis, the mitotic index calculation, the counting number of atypical mitosis and the degree of organ regeneration ability. Dynamics of these liver changes at infection process in experimental animals caused by Yersinia pestis plasmid variants was investigated in this work. The variability of liver injuries was shown depending on plasmid-associated virulence of the infection agent. It was proved that the Y. pestis strain carrying three basic pYP (6 mDa), pYV (45 mDa), pYT (61 mDa) plasmids caused the most severe systemic disease with lethal outcome as a rule. Lack of species-specific plasmids and especially virulence and pathogenicity plasmids reduced the rate of infection process generalization and the ability of the pathogen to initiate pathological changes incompatible with the microorganism life. Therefore, all morphological liver changes in experimental plague infection are directly dependent on plasmid profile of the pathogen. The mechanism of toxicity included the damaging effect of the toxin to the cellular structures and failure of the metabolic processes in the organism. Acuity of intoxication and the development of pathological process can be estimated by exploring changes in liver morphology.